Analisis Implementasi Penilaian Autentik Portofolio dalam Pembelajaran IPA - suhelayanti, Suhelayanti (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
This study aims to determine the implementation of authentic portfolio assessment in science learning. This research is descriptive qualitative. Methods used for data collection include observation, interviews, and documentation. Data reduction, data presentation, and data verification are theoretical techniques used in data analysis by Miles and Huberman. The results showed that the implementation of authentic portfolio assessment in science learning has gone well, this is in accordance with the authentic portfolio steps, if it is in accordance with the authentic portfolio steps, then the implementation of the authentic portfolio has gone well.